PENINGKATAN EKSISTENSI MAKANAN TRADISIONAL SUNDA MELALUI OPERASI PASAR BUHUN DI DESA SELAWANGI - Muna Munipati Sukma, Viana; Ristri Alkhila, Intan (Penerbit Lafadz Jaya, 2022)
Traditional food usually has a philosophical meaning, but the existence and existence of traditional food is decreasing day by day, there is a need for innovation so that it can attract people to want to know to find traditional food to enjoy. With the innovation of places such as markets that sell a variety of traditional foods with place designs that are made more attractive or blended with a touch of modern touch. The position of the data investigator is the process of compiling in a coherent manner the data that is obtained from the product of interviews, summaries and archiving in the form of organizing instructions. Buhun Market is a market that provides a variety of traditional foods organized by the village of Selawangi. This Buhun Market can also be referred to as a village creative economy because it is carried out by village managers such as the Village Chair and his staff. The buhun market is designed in such an attractive way with a typical Sundanese interior as well. In order to increase the existence of traditional foods, innovation is needed to attract people to want to know or make it easier to find traditional foods that they will enjoy. One of them is the innovation of places such as markets that sell a variety of traditional foods, with place designs that are more attractive or mixed with a touch of modern style.